3D-printed external fixation guide combined with video-assisted thoracoscopic surgery for the treatment of flail chest: a technical report and case series - Hu, Meng; Sun, Maolin; Bao, Chuanen; Luo, Junlong; Zhuo, Longcai; Guo, Ming (Frontiers in Surgery, 2023)
Background Flail chest is a common and serious traumatic condition in thoracic surgery. The treatment of flail chest often includes open reduction and internal fixation, which is relatively traumatic, complicated, and expensive. As three-dimensional (3D) printing technology is widely used in the clinical field, the application of 3D-printed products to chest trauma will become a new treatment option. To date, the use of 3D-printed external fixation guides for flail chests has not been reported. Thus, we aimed to assess the short-term efficacy of a new technology that treated flail chests with an individualized 3D-printed external fixation guide combined with video-assisted thoracoscopic surgery (VATS). Patients and methods A retrospective analysis was performed on patients with flail chest treated with this new technique at our center from January 2020 to December 2022. The following parameters were included: operative time, thoracic tube extraction time, intensive care unit time, thoracic volume recovery rate, visual analog scale score 1 month postoperatively, and postoperative complication rate. All patients were followed up for at least 3 months. Results Five patients (mean age: 45.7 years) were enrolled; they successfully underwent surgery without chest wall deformity and quickly returned to daily life. The average number of rib fractures was 8.4; all patients had lung contusion, hemopneumothorax, and anomalous respiration. The abnormal breathing of all patients was completely corrected on postoperative day 1, and the chest wall was stable. One case experienced mild loosening of the 3D-printed guide postoperatively; however, the overall stability was not affected. The other four cases did not experience such loosening because we replaced the ordinary silk wire with a steel wire. All cases were discharged from the hospital 2 weeks postoperatively and returned to normal life 1 month after the removal of the 3D-printed guide on average. Only one case developed a superficial wound infection postoperatively, and no perioperative death occurred. Conclusions The 3D-printed external fixation guide combined with video-assisted thoracoscopic surgery is a novel technique in the treatment of flail chest and is safe, effective, feasible, and minimally invasive, with satisfactory clinical efficacy.